Biochemical Analysis of Age-Related Hormonal Changes and Their Impact on Metabolic Pathways - A Cross-Sectional Study - HAIDER, SYED NAVEED; RAZIA BATOOL,; SHUJA, NAVEED; QURATULAAIN ZOHRA,; AQEELA KOUSAR,; M. AKEEL, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Gradual changes in hormonal levels with aging are associated with severe changes in biochemical pathways controlling metabolic, protein synthesis, and energy balance. A basic understanding of these age related hormonal changes is necessary to early detection of metabolic disorders and age specific therapeutic intervention. Aim: Biochemically evaluate the relationship between metabolic pathway disturbances due to age-related hormonal changes in a population of 100 individuals from different age groups. Methodology: This was a descriptive, cross sectional study done from July to December 2024 at the Department of Biochemistry, Lahore Medical & Dental College Lahore. A total of 100 patients were enrolled and divided into three age groups: young adults (20–35 years), middle aged adults (36–60 years) and elderly patients (>60 years) in an equal proportion. Levels of insulin, cortisol, thyroid hormones (T3, T4, and TSH), testosterone (males), estrogen (females), IGF-1 and growth hormone were analyzed from fasting venous blood samples. Results: The elderly group showed significant decline in IGF-1 (p<0.001), testosterone (p<0.01), estrogen (p<0.05) and growth hormone (p<0.001) compared to younger subjects. With increasing age (p< 0.05), the levels of cortisol and TSH increased slightly, but statistically, these levels were slightly increased. There were corresponding changes in metabolic markers including elevated fasting glucose and total cholesterol in the elderly group (p<0.01). IGF-1 and HDL levels showed positive correlation and cortisol and insulin sensitivity markers showed negative correlation. Conclusion: Hormonal shifts associated with age have a significant impact on metabolism. Older individuals may be predisposed to insulin resistance, dyslipidemia and altered liver and renal biochemistry as a result of declining anabolic hormones, increased catabolic hormone levels.